Pyrogenic carbon accelerates iron cycling and hydroxyl radical production during redox fluctuations of paddy soils - Danyu Huang; Ning Chen; Yuan Lin; Chenghao Ge; Xiaolei Wang; Dixiang Wang; Changyin Zhu; Guodong Fang; Dongmei Zhou (Biochar, 2023)
Abstract Carbon materials (e.g., pyrogenic carbon (PyC)) are widely used in agricultural soils and can participate in various biogeochemical processes, including iron (Fe) cycling. In soils, Fe(II) species have been proposed as the main active contributor to produce reactive oxygen species (ROS), which are involved in various biogeochemical processes. However, the effects of PyC on the transformation of different Fe species in soils and the associated production of ROS are rarely investigated. This study examined the influence of PyC (pyrolyzed at 300–700 °C) on Fe(II)/Fe(III) cycling and hydroxyl radical (·OH) production during redox fluctuations of paddy soils. Results showed that the reduction of Fe(III) in soils was facilitated by PyC during anoxic incubation, which was ascribed to the increased abundance of dissimilatory Fe(III)-reducing microorganisms (biotic reduction) and the electron exchange capacity of PyC (abiotic reduction). During oxygenation, PyC and higher soil pH promoted the oxidation of active Fe(II) species (e.g., exchangeable and low-crystalline Fe(II)), which consequently induced higher yield of ·OH and further led to degradation of imidacloprid and inactivation of soil microorganisms. Our results demonstrated that PyC accelerated Fe(II)/Fe(III) cycling and ·OH production during redox fluctuations of paddy soils (especially those with low content of soil organic carbon), providing a new insight for remediation strategies in agricultural fields contaminated with organic pollutants. Graphical Abstract